Research advances of pericytes in renal interstitial fibrosis - Feng Yi-duo; Diao Zong-li; Liu Wen-hu (Linchuang shenzangbing zazhi)
Pericytes are mesenchymal cells in contact with endothelial cells and partially embedded in the basement membrane of blood vessels.Pericytes possess the capability of differentiating and their surface markers change according to different tissues，various developmental stages and diverse pathophysiological environments.Numerous studies have demonstrated that pericytes are a major source of kidney myofibroblasts and multiple signal pathways are involved in the process of pericytes/fibroblasts transdifferentiation into myofibroblasts.Pericyte-endothelial cell interaction also plays an important role in the development of renal fibrosis.This review summarized the latest advances of pericytes in the pathogenesis of renal intestitial fibrosis and targeted therapy for pericytes may be an effective anti-kidney fibrosis strategy.